Gene-gene interaction of BLK, TNFSF4, TRAF1, TNFAIP3, and REL in systemic lupus erythematosus - Zhou, Xu-jie; Lu, Xiao-lan; Nath, Swapan K.; Lv, Ji-cheng; Zhu, Sai-nan; Yang, Hai-zhen; Qin, Lian-xiang; Zhao, Ming-hui; Su, Yin; Shen, Nan; Li, Zhan-guo; Zhang, Hong (Arthritis & rheumatology (Hoboken, N.J.), 2012)
Objective Although the number of convincingly established genetic associations with systemic lupus erythematosus (SLE) has increased sharply over the last few years, refinement of these associations is required, and their potential roles in gene–gene interactions need to be further investigated. Recent genome‐wide association studies (GWAS) in SLE have produced renewed interest in B cell/T cell responses and the NF‐κB signaling pathway. The aim of this study was to search for possible gene–gene interactions based on identified single‐nucleotide polymorphisms (SNPs), in using an approach based on the role of signaling pathways. Methods The SNPs in BLK, TNFSF4, TRAF1, TNFAIP3, and REL were replicated in order to evaluate genetic associations with SLE. TaqMan genotyping was conducted in 804 Chinese patients with SLE and 722 matched control subjects. A multiple logistic regression model was used to estimate the multiplicative interaction effect of the SNPs, and additive interactions were analyzed by 2 × 2 factorial designs. Data from a previously published GWAS conducted by the International Consortium on the Genetics of Systemic Lupus Erythematosus were derived for comparison and validation. Results Single‐marker analysis validated the association of BLK rs2736340 (P = 4.25 × 10−6) as well as TNFSF4 rs2205960 (P = 2.82 × 10−5) and TNFAIP3 rs5029939 (P = 1.92 × 10−3) with SLE susceptibility in Chinese. Multiplicative interaction analysis indicated that BLK had an interactive effect with TNFSF4 in Chinese patients with SLE (P = 6.57 × 10−4). Additive interaction analysis revealed interactions between TRAF1 and TNFAIP3 in both Chinese (P = 2.18 × 10−3) and Caucasians (P = 2.86 × 10−4). In addition, multiple tendencies toward interactions were observed, and an additive effect was observed as the number of risk genotypes increased. Conclusion The results of this study provide evidence of the possible gene–gene interactions of BLK, TNFSF4, TRAF1, TNFAIP3, and REL in SLE, which may represent a synergic effect of T cells and B cells through the NF‐κB pathway in determining immunologic aberration.